2021
DOI: 10.3389/fphar.2021.806002
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decrease in Abdominal Pain and Associated Structural- and Functional Mechanisms: An Exploratory Study in Healthy Individuals and Irritable Bowel Syndrome Patients

Abstract: Introduction: The world population is ageing, resulting in increased prevalence of age-related comorbidities and healthcare costs. Limited data are available on intestinal health in elderly populations. Structural and functional changes, including altered visceroperception, may lead to altered bowel habits and abdominal symptoms in healthy individuals and irritable bowel syndrome (IBS) patients. Our aim was to explore age-related changes in gastrointestinal symptoms and underlying mechanisms.Methods: In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Similarly, a 2012 meta‐analysis of 14 studies demonstrated that IBS was more prevalent in those under 50 years of age, compared to those over 50 50 . Our results extend upon these findings, demonstrating that not only may FGID prevalence be greater in younger adult age groups, but FGID overlap is also more prevalent perhaps partly due to greater visceral hypersensitivity in younger patients 51,52 …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, a 2012 meta‐analysis of 14 studies demonstrated that IBS was more prevalent in those under 50 years of age, compared to those over 50 50 . Our results extend upon these findings, demonstrating that not only may FGID prevalence be greater in younger adult age groups, but FGID overlap is also more prevalent perhaps partly due to greater visceral hypersensitivity in younger patients 51,52 …”
Section: Discussionsupporting
confidence: 79%
“…50 Our results extend upon these findings, demonstrating that not only may FGID prevalence be greater in younger adult age groups, but FGID overlap is also more prevalent perhaps partly due to greater visceral hypersensitivity in younger patients. 51,52 Increasing FGID overlap was strongly associated with worse quality of life in our study, in both the overall constipation analysis and FDD sub-analysis. Reductions in quality of life were particularly strong in domains that assessed the impact of poor health on exercise capacity, employment, activities of daily living, social interactions, and community involvement, 33 which are important factors for future health and independence.…”
Section: Discussionsupporting
confidence: 50%
“…Previous data found that the prevalence of FGIDs decreased with age in Internet survey countries 3 (which may be related to age‐related decrease in abdominal pain perceptions 10 ). We observed increased prevalence of prescription pain medication usage with age.…”
Section: Discussionmentioning
confidence: 94%
“…Research on disease activity patterns for IBD is scarce, but suggests a more intermittent or even chronic inflammation pattern in newly diagnosed CD patients 31 . In IBS, it has previously been shown that abdominal pain may attenuate over time in patients who get older or have a longer duration of symptoms 32 . Acceptance of diagnosis or symptoms over the years may play a role in the perception of pain.…”
Section: Discussionmentioning
confidence: 99%